High-speed demonstration of an output interface driver for single-flux quantum systems. - Harada, N.
The high-speed operation of a one-channel output interface for a single-flux quantum (SFQ) system has been demonstrated. The interface consisted of a Josephson latching driver, a room-temperature semiconductor amplifier, and a decision circuit module. The Josephson latching driver was fabricated by using a 2.5-kA/cm2 standard Nb junction process and used to amplify an SFQ pulse into a 5.5-mV level signal at 10 Gb/s. The interface converted the SFQ pulse signal into a nonreturn-to-zero signal having an amplitude of 1 V at 10 Gb/s
Keywords: 1 V; 10 Gbit/s.; 5.5 mV; Josephson latching driver; Josephson logic; Nb; Nb junction process; SFQ pulse signal; Decision circuit module; High-speed operation; Nonreturn-to-zero signal; One-channel output interface; Output interface driver; Room-temperature semiconductor amplifier; Single-flux quantum system